Analysis of The Dynamic Stability Positioning Control System of Semisubmersible - Aulia siti Aisjah; Eko Budi Djatmiko; Riza Aris Hikmadiyar; Nur Kholis (IPTEK Journal of Proceedings Series, 2015)
The semisubmersible offshore dynamics depend on the condition of the ocean environments. Disruption of forces and moments in the floating structure caused by environment factors, there are wind, waves and ocean currents. This disturbances will cause decreased stability of the structure. This situation will disrupt the process of oil and gas exploration. Currently exploration activities is success if the structure in the static condition and remain on. This condition needs a force or torque to counter the disruption caused by the environment. This paper proposes a control system and analyze the performance of response stability of dynamic positioning system (DPS). DPS will control in 3 Degree of Freedom (DOF) variables, there are: sway, roll and yaw. The structure of the DPS consists of controllers, sensors, actuators. Actuators are Thruster System and Power System. The strategic to maintain in DPS is Linear Quadratic (LQG) control. This method is one of optimal control which capable rejected wave interference. Some values control parameters, that are Q and R in the cost function, show the robustness of DPS.